2010
DOI: 10.1002/pnp.163
|View full text |Cite
|
Sign up to set email alerts
|

Computerised cognitive behavioural therapy and its uses

Abstract: The use of computer software programmes to deliver cognitive behavioural therapy to people with mental health disorders is becoming increasingly popular. Here the authors describe what conditions computerised cognitive behavioural therapy may be useful for, discuss its advantages and disadvantages and outline the current NICE guidance on its use. Copyright © 2010 Wiley Interface Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Computer-delivered therapy, including computerized CBT, has become increasingly popular in recent years and holds substantial promise for increasing access to effective treatment options for both depression and social anxiety [ 11 ]. One of its major advantages lies in its accessibility to individuals who experience geographic, financial, or personal challenges for human-delivered therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-delivered therapy, including computerized CBT, has become increasingly popular in recent years and holds substantial promise for increasing access to effective treatment options for both depression and social anxiety [ 11 ]. One of its major advantages lies in its accessibility to individuals who experience geographic, financial, or personal challenges for human-delivered therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SCD may benefit from behavioral interventions that can be accessed on computers or mobile phones. Specifically, computerized CBT (cCBT) adapts traditional tenets of CBT into an interactive e-learning online experience that teaches users how to manage their mood through lessons, exercises, and quizzes [28,29]. Internet-delivered cCBT has been proven effective in reducing depression and anxiety [30,31]; however, few CCBT trials have included nonwhite participants [32], and no studies have tested cCBT among adults with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Several computerbased treatments have been examined in the treatment of depression, anxiety disorders, and insomnia [24][25][26][27] and range from self-guided web-based tools 28 to interactive modules that augment traditional cognitive-behavioral therapy (CBT) (e.g., computer-assisted CBT, CCBT). [29][30][31][32] Although, the past decade has seen significant growth in and tailoring of computerbased treatments to specific populations, 33,34 perinatal women have not been frequently included. [35][36][37] Like others, 32 our previous trial of CCBT for depressed pregnant women showed a high rate of adherence to the treatment program, and 80% of participants showed symptom improvement, 31 suggesting that computer-based treatments may be a promising option for perinatal women.…”
Section: Introductionmentioning
confidence: 99%